2007
DOI: 10.1074/jbc.m703173200
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Nucleotide Phosphodiesterase PDE1C1 in Human Cardiac Myocytes

Abstract: Isoforms in the PDE1 family of cyclic nucleotide phosphodiesterases were recently found to comprise a significant portion of the cGMP-inhibited cAMP hydrolytic activity in human hearts. We examined the expression of PDE1 isoforms in human myocardium, characterized their catalytic activity, and quantified their contribution to cAMP hydrolytic and cGMP hydrolytic activity in subcellular fractions of this tissue. Western blotting with isoform-selective anti-PDE1 monoclonal antibodies showed PDE1C1 to be the princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 52 publications
(27 reference statements)
5
101
0
3
Order By: Relevance
“…This is presumed to be attributable to increased cGMP in one or more compartments in the heart. It has been shown that these same concentrations of SIL also inhibit PDE-1C activity by ∼20% in heart extracts (58). It is also reported that SIL treatment increases cardiac cGKI activity efficiently, although it is not clear that this occurs in the CM (34).…”
Section: Discussionmentioning
confidence: 97%
“…This is presumed to be attributable to increased cGMP in one or more compartments in the heart. It has been shown that these same concentrations of SIL also inhibit PDE-1C activity by ∼20% in heart extracts (58). It is also reported that SIL treatment increases cardiac cGKI activity efficiently, although it is not clear that this occurs in the CM (34).…”
Section: Discussionmentioning
confidence: 97%
“…A PDE1-selective inhibitor (IC86340) blunts the hypertrophic response. These results are highly relevant since PDE1 provides the majority of cGMP-hydrolyzing activity in the heart (259,388,389,395) and acts to counter the cytoprotective effects of cGMP signaling through cGMP-dependent protein kinase (PKG).…”
Section: Calmodulin-binding Phosphodiesterases (Pde1)mentioning
confidence: 99%
“…Vinpocetine, the best known PDE1 inhibitor, has been used clinically in some places but has poor cell penetration properties and a significant toxicity profile. Most PDE5-selective inhibitors also inhibit PDE1, which becomes problematic when high extracellular concentrations are used (388,389). ICOS Corporation (now a part of Eli Lilly Corporation) has produced two selective and potent PDE1 inhibitors (IC229 and IC224 with IC 50 values of 560 and 800 nM, respectively) (249, 388, 389).…”
Section: Pde1 Inhibitorsmentioning
confidence: 99%
“…15 There are 3 isoforms (PDE1A, PDE1B and PDE1C), all expressed in cardiac myocytes. 16,17 PDE1A and PDE1B hydrolyze cGMP with higher affinity than cAMP, whereas PDE1C, the dominant isoform in human cardiac myocytes, hydrolyzes both with similar affinity. 17 Although PDE1 is a major esterase for both cAMP and cGMP in the myocardium or cardiac myocytes in humans, 16,18 its physiological effect, particularly in vivo, has not been fully clarified.…”
Section: Degradation By Pdesmentioning
confidence: 99%